KARAKTERISTIK POTENSI ANGIN SEBAGAI SUMBER ENERGI TERBARUKAN DI INDONESIA DARI DATA SATELIT REMOTE SENSING - I Ketut Swardika (P3M Politeknik Negeri Indramayu, 2019)
Global warming, climate changes mostly associates with solar-renewable energy; however wind-energy potential has no detail reports in Indonesia. This study aims to mapping of characteristics and potential of wind as renewable-energy from long-term (1997-2009) satellite remote-sensing. Wind direction (WD), speed (WS) derives from microwave/ scatterometer sensor on satellite operational years as follows: ADEOS (1997), DMSP (1998-1999), AMI (1997-1999), QuikSCAT (1999- 2009). Data processed into 0.25o grid, monthly temporal resolution. The regional characteristics of WD/WS, seasonal and zonal-longitudinal reveals by statistic. Electrical energy derives from kinetic energy of turbine-blades per-unit time. Energy conversion uses power-curves and technical parameters of 1.50 and 3.40 MW (GE 1.5s, 3.4-137 models) onshore installations with 25km2 per point, 15% availability area. Result shows WS has low characteristics in Indonesian-waters (<3.7ms-1). WS has high at north-south Java-Sumatra, Banda waters (<6.9ms-1). The zonal-seasonal wind variability of WD, WS stables at equator. Increases of degree-zonal (>5deg), wind curve follows north-south hemisphere characteristics and crosses in April, October. The north-west, south-east monsoon shows clearly only on north-western of Java-Sumatra waters. WS has range of 0-25.20ms-1, average 6.64ms-1 with Std. 1.64ms-1. With these WS, generation of electrical energy has range from 104.0 to 2230.5 kWh per-point installation grid.